Study of Chemical and Organoleptic Properties of Breadfruit (Artocarpus communis) Flour Crackers - Lumbessy, Abd. Syukur; Masuku, Mustamin Anwar; Hirto, Susilawati (Agrikan Jurnal Agribisnis Perikanan, 2023)
The high use of wheat flour in foodstuffs has led to dependence on wheat flour. Alternative food procurement efforts are needed to overcome this problem. One alternative that can be done is to substitute flour with other flour. In order to reduce people's dependence on wheat flour, considering that Indonesia is not a wheat-producing country, it is very necessary to process various kinds of natural carbohydrates which are processed into food ingredients to replace wheat flour. This research has several stages, namely the first stage of making breadfruit flour, the second stage of making crackers. This study used a completely randomized design with one factor consisting of 5 treatments with substitution of breadfruit flour. The formulation is P0 (100% flour: 0% breadfruit flour), P1 (75% wheat flour : 25% breadfruit flour), P2 (wheat flour 50% : breadfruit flour 50%), P3 (wheat flour 25% : breadfruit flour 75%) and P4 (0% wheat flour : 100% breadfruit flour). Parameters observed were chemical properties test, and organoleptic. This study obtained crackers from substitution of breadfruit flour to produce water content7,53%-9,30%, ash content2,87%-3,89%, fat content15,48%-18,16%, as much protein4,10%-7,37%, carbohydrate levels119,87%-126,47%. As for the organoleptic include color3,56-4,01 (rather like), aroma3,08-3,61 (neutral), taste3,60-3,84 (neutral) and texture3,40-3,99 (neutral) with the best formulation found in treatment P1.